2021
DOI: 10.1128/aac.01121-21
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Multidrug Resistance in Plasmodium falciparum: a Longitudinal Study of Genetic Resistance Markers in the Greater Mekong Subregion

Abstract: Increasing drug resistance in Plasmodium falciparum to artemisinins and their ACT partner drugs jeopardises effective antimalarial treatment. Resistance is worst in the Greater Mekong Subregion. Monitoring genetic markers of resistance can help to guide antimalarial therapy. Markers of resistance to artemisinins ( PfKelch mutations), mefloquine (amplification of P. falciparum multidrug resistance-1, PfMDR1, ), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Since its emergence in 2009, artemisinin resistance exerted strong selection effects on the GMS P. falciparum population due to a continuous drug pressure resulting from intensive high-coverage treatment programmes implemented by all countries in the region 11 , 43 , 70 . There is now a clear distinction between the P. falciparum population in the wGMS (Myanmar, Thai-Myanmar border, and Bangladesh) and eGMS (Cambodia Laos and Southern Vietnam), the latter of which likely provided the supporting genetic background for artemisinin resistance 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Since its emergence in 2009, artemisinin resistance exerted strong selection effects on the GMS P. falciparum population due to a continuous drug pressure resulting from intensive high-coverage treatment programmes implemented by all countries in the region 11 , 43 , 70 . There is now a clear distinction between the P. falciparum population in the wGMS (Myanmar, Thai-Myanmar border, and Bangladesh) and eGMS (Cambodia Laos and Southern Vietnam), the latter of which likely provided the supporting genetic background for artemisinin resistance 40 .…”
Section: Discussionmentioning
confidence: 99%
“…ACT combines a highly potent, rapidly cleared artemisinin derivative and a less potent, slowly cleared partner drug such as lumefantrine, amodiaquine, piperaquine, pyronaridine or mefloquine. A worrying recent development is multidrug resistance that has emerged to these artemisinin and partner drug combinations and is now spreading through large regions of Southeast Asia [ 7 – 9 ]. In response, policy makers in Cambodia, the country with the highest burden of multidrug-resistant malaria, opt to switch between ACTs when treatment failure is observed [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ampli cation of plasmepsin-2 is widely used as a marker to trace PPQ resistance [9,[12][13][14][15]. Previous studies suggested that this genotype was restricted to eastern GMS [10,14,15]. Consistent with these reports, none of the P. falciparum isolates in Tak province from 2013-2019 had plasmepsin-2 ampli cation.…”
Section: Discussionmentioning
confidence: 66%